Curcumin enhances the production of major structural components of elastic fibers, elastin, and fibrillin-1, in normal human fibroblast cells. Issue 2 (1st February 2015) - Lee, Shu-Mei; Chiang, Shu-Hua; Wang, Hsun-Yen; Wu, Pey-Shiuan; Lin, Chih-Chien
Abstract: Curcumin is the major component of the yellow extract derived from the rhizome of the Curcuma longa, which is also a main bioactive polyphenol and has been generally used as a spice, food additive, and herbal medicine. In this presented study, we found that curcumin can enhance the production of major structural components of elastic fibers, elastin, and fibrillin-1, in normal human fibroblast cells via increasing ELN and FBN1 promoters' activities. With 2 μM curcumin treatment, the enhanced tropoelastin and fibrillin-1 protein amounts in Detroit 551 cells were approximately 134 and 130% of control, respectively. Therefore, our results demonstrated that curcumin may be used as a functional compound and applied to drugs, foods, and cosmetics in the future. Graphical abstract: : Curcumin, a major compound of the yellow extract derived from the rhizome of the Curcuma longa . It can enhance the production of major structural components of elastic fibres, elastin and fibrillin-1, in normal human fibroblast cells by increasing the transcriptions.